DIGITALIZATION AND BIG DATA IN PREVENTING CORRUPTION IN EDUCATION SECTOR: TOWARDS INCLUSIVE AND EQUITABLE EDUCATION - Aditya Wirawan; Elvrida N Sinaga (Scientia Integritas Utama, 2022)
Corruption in the education sector is a big question considering enacting the education and anti-corruption laws. The substantial education fund in Indonesia is to increase human resources as the principal capi-tal in national development. It is necessary and urgent to answer why and how digitalization and Big Data can prevent corruption in the edu-cation sector from achieving inclusive and equitable quality education in Indonesia. This paper is a normative juridical study with an interdisciplinary approach. The ultimate goal is to apply digitalization and Big Data rules to narrow the space for corruption and predict and control social phenomena in the education sector. The existing regulations in the management of education funds are only repressive and not adequate in terms of prevention which will be effective and efficient when involving technology (especially digitalization and Big Data in the education sector). The burden of this paper lies in the study, which is still normative and qualitative. An empirical study with a quantitative approach is needed, but this study is sufficient to enrich the literature for future empirical studies. The existence of digitalization rules and Big Data in national education controlled by the Chief Digital Officer can prevent corruption in the education sector. It can be a means of checks and balances and succeed in the framework of every education policy carried out by the government, whose primary output and outcome is the use of funds targeted to education and the achievement of inclusive and equitable quality education in Indonesia by 2030.